Examining Emotional Intelligence, Perceived Organizational Support, and Job Satisfaction on Job Performance - Eko Setiyono; Aryana Satrya (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study explores how emotional intelligence and perceived organizational support influence job performance among government employees, focusing on the mediating role of job satisfaction. The research targets civil servants at the directorate general of customs and excise in Indonesia, where complex regulatory demands and public service expectations create high pressure. The objective is to examine direct and indirect effects of these factors on performance and satisfaction in a public sector context. A quantitative approach was used, collecting data from 249 respondents through cross-sectional surveys. Analysis employed partial least squares structural equation modeling with SmartPLS 4 software, applying bootstrapping and blindfolding procedures. Results show that emotional intelligence positively affects both job satisfaction and job performance directly. Perceived organizational support significantly improves job satisfaction but has no direct impact on job performance. Job satisfaction positively influences job performance and mediates the relationships between emotional intelligence, perceived organizational support, and job performance. These findings highlight job satisfaction as a key psychological mechanism linking individual and organizational factors to better employee outcomes in public institutions.